Paradigma Pembelajaran IPS Dan Permasalahannya - Sina, Ainun; Dini, Alifah; Nurhalimah, Nurhalimah (Faidatuna, 2023)
Learning is a process of thinking and acting and is a change in behavior that is relatively fixed and the result of repeated practices. In learning there are goals to be achieved both in terms of knowledge and attitudes to be formed in students. In each process there are obstacles and problems that will be faced. In Social Studies learning, Social Sciences is not an independent science or a single science like other social sciences, but the material in Social Sciences uses social science materials that are selected and adapted to the goals of teaching and education. IPS is taught to students to be a way of developing students' personal development, namely developing students' potential, physical, social, and emotional. The difficulties experienced by students in learning are common and often occur or are experienced by students, whether it is motivated by various specific factors so that students have difficulties in understanding social studies learning. For this reason, by understanding the IPS learning paradigm and its problems, it is hoped that it will be able to broaden knowledge and be able to overcome existing problems.